THE EFFECT OF EYE GYMNASTICS ON COMPUTER VISION SYNDROME IN EMMAUS SURABAYA FEMALE DORMITORY STUDENTS - Woge, Kanisia Vermina; Cicilia Wahju Djajanti; Ni Luh Agustini Purnama (Indonesian Journal of Community Health Nursing, 2025)
The used of gadgets was increased greatly, gadgets have many benefits in the world of education, especially for students in the learned process. Excessive used of gadgets can cause complained of eye disorders called computer vision syndrome. The phenomenon found in female students at the Emaus Putri Dormitory in Surabaya, was that most of them experienced computer vision syndrome. One of the efforted to prevented and overcome computer vision syndrome was to did eye exercised. This studied aimed to determined the effected of eye exercised on computer vision syndrome. The method used was pre-experimental with a one-group-pre-post-test design researched design. The independent variable was eye exercised and the dependent variable was computer vision syndrome. The sample size was took used a total sampling technique with a sample of 44 female students at the Emaus Girls' Dormitory Surabaya. The instrument used was the CVS-Q questionnaire and used the Wilcoxon statistical test. Based on the results of the study before eye exercised, 38 (82%) respondents experienced computer vision syndrome, and after eye exercised, the number of respondents who experienced computer vision syndrome decreased to 17 (39%). The results of the Wilcoxon test showed a p value of (0.000) < α (0.05) which means that eye exercised have an effected in reduced the score of computer vision syndrome. By to eye exercised regularly can reduced the symptoms of computer vision syndrome. Keywords: Computer Vision Syndrome, Eye Exercises